Cognitive enhancement and academic misconduct: a study exploring their frequency and relationship - Dubljević, Veljko (Ethics & behavior, 2014)
We investigated the acceptability and use frequency of cognitive enhancement medication and three different types of academic misconduct (plagiarism, cheating, and falsifying/fabricating data). Data collected from a web-based survey of German university students were used in our analysis. Moral acceptability of cognitive enhancers was relatively low and moderate for academic misconduct. The correlation between these measures was moderately weak. The use frequency of cognitive enhancers was lower than for academic misconduct and was (very) lightly correlated with the occurrences of reported plagiarism and fabrication/falsification. A higher acceptability of each act was associated with a higher use frequency of each act.